2014
DOI: 10.3389/fnbeh.2014.00242
|View full text |Cite
|
Sign up to set email alerts
|

Rat thalamic neurons encode complex combinations of heading and movement directions and the trajectory route during translocation with sensory conflict

Abstract: It is unknown how thalamic head direction neurons extract meaningful information from multiple conflicting sensory information sources when animals run under conditions of sensory mismatch. In the present study, rats were placed on a treadmill on a stage that moved in a figure-8-shaped pathway. The anterodorsal and laterodorsal neurons were recorded under two conditions: (1) control sessions, in which both the stage and the treadmill moved forward, or (2) backward (mismatch) sessions, in which the stage was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…These observations suggest that laterodorsal thalami are additionally influenced by non-visual, local maze cues, which is consistent with the observation that laterodorsal thalamic neurons fire in relation to somatosensory cues such as vibrissae stimulation (Bezdudnaya & Keller, 2008). In addition, a recent report indicated that subpopulations of directional cells in the laterodorsal thalamus fire along specific environmental routes and in specific forward or backward movement directions (Enkhjargal et al, 2014), and experiments using axonal calcium imaging indicate that the lateroposterior thalamus conveys movement related information to cortical regions, including locomotion speed, saccadic-related movements, and optic flow (Roth et al, 2016). Collectively, these observations parallel the diversity of neural firing in the primary input region of the lateral thalamus, the superior colliculus, which reportedly contains neurons that discharge in relation to a number of somatosensory-motor events, including egocentric body turns (e.g., turn left or turn right), and the direction of movement, e.g., toward the center of the maze vs. away from the center (Cooper et al, 1998).…”
Section: Anterior-lateral Thalamus and Electrophysiology In Behaving supporting
confidence: 71%
“…These observations suggest that laterodorsal thalami are additionally influenced by non-visual, local maze cues, which is consistent with the observation that laterodorsal thalamic neurons fire in relation to somatosensory cues such as vibrissae stimulation (Bezdudnaya & Keller, 2008). In addition, a recent report indicated that subpopulations of directional cells in the laterodorsal thalamus fire along specific environmental routes and in specific forward or backward movement directions (Enkhjargal et al, 2014), and experiments using axonal calcium imaging indicate that the lateroposterior thalamus conveys movement related information to cortical regions, including locomotion speed, saccadic-related movements, and optic flow (Roth et al, 2016). Collectively, these observations parallel the diversity of neural firing in the primary input region of the lateral thalamus, the superior colliculus, which reportedly contains neurons that discharge in relation to a number of somatosensory-motor events, including egocentric body turns (e.g., turn left or turn right), and the direction of movement, e.g., toward the center of the maze vs. away from the center (Cooper et al, 1998).…”
Section: Anterior-lateral Thalamus and Electrophysiology In Behaving supporting
confidence: 71%
“…Seven Wistar male rats weighing 200–300 g were used. The animals were similarly treated according to our previous protocols ( Dayawansa et al, 2006 ; Zou et al, 2009 ; Enkhjargal et al, 2014 ). They were individually housed in cages controlled at a constant temperature (20 ± 2°C) with free access to water and laboratory chow.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggest that theta rhythm is implicated in both the encoding and retrieval of information in the HF ( Hasselmo et al, 2002 ; Manns et al, 2007b ; Terada et al, 2017 ) and also in modulation of HF synaptic current during learning ( Brankack et al, 1993 ; Wyble et al, 2000 ; Orr et al, 2001 ), suggesting that HF theta waves might reflect the activity of a HF comparator during navigation ( Zou et al, 2009 ). In our previous studies, to analyze HF theta rhythm and thalamic head direction cell activity in a mismatch condition, rats locomoted on a treadmill that was translocated along a figure 8-shaped track by a motion stage ( Zou et al, 2009 ; Enkhjargal et al, 2014 ). In a mismatch condition, although rats locomoted forward on the treadmill, the treadmill itself was translocated backward ( Zou et al, 2009 ; Enkhjargal et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linguistic thalamus in fact responds to complex permutations [62], transmits cortico-cortically [63], sharpens the focus through the CSTCs, joins cognitive and motor processing [64], chooses words [65] or syntax [66] intending minimized efforts [67]. Direct tracts connect Broca's region to the anterior thalamus [68].…”
Section: The Thalamus Emerges As Syllogistic Speakermentioning
confidence: 99%